Discovery of a Novel Mycobacterial F‐ATP Synthase Inhibitor and its Potency in Combination with Diarylquinolines. Issue 32 (26th May 2020) - Hotra, Adam; Ragunathan, Priya; Ng, Pearly Shuyi; Seankongsuk, Pattarakiat; Harikishore, Amaravadhi; Sarathy, Jickky Palmae; Saw, Wuan‐Geok; Lakshmanan, Umayal; Sae‐Lao, Patcharaporn; Kalia, Nitin Pal; Shin, Joon; Kalyanasundaram, Revathy; et al.
Abstract: The F1 FO ‐ATP synthase is required for growth and viability of Mycobacterium tuberculosis and is a validated clinical target. A mycobacterium‐specific loop of the enzyme's rotary γ subunit plays a role in the coupling of ATP synthesis within the enzyme complex. We report the discovery of a novel antimycobacterial, termed GaMF1, that targets this γ subunit loop. Biochemical and NMR studies show that GaMF1 inhibits ATP synthase activity by binding to the loop. GaMF1 is bactericidal and is active against multidrug‐ as well as bedaquiline‐resistant strains. Chemistry efforts on the scaffold revealed a dynamic structure activity relationship and delivered analogues with nanomolar potencies. Combining GaMF1 with bedaquiline or novel diarylquinoline analogues showed potentiation without inducing genotoxicity or phenotypic changes in a human embryonic stem cell reporter assay. These results suggest that GaMF1 presents an attractive lead for the discovery of a novel class of anti‐tuberculosis F‐ATP synthase inhibitors. Abstract : TB or not TB : The antimycobacterial compound GaMF1 inhibits the mycobacterial F‐ATP synthase by binding to a specific loop of subunit γ, preventing ATP synthesis. GaMF1 is active against multidrug‐resistant Mycobacterium tuberculosis strains and increases the potency of the TB drug bedaquiline and its analogues, thereby offering potential for an efficient multidrug combination. Medicinal chemistry efforts gave analogues with nanomolar potency.